GOVERNING THE COAST: LESSONS FROM GERMANY FOR DEVELOPING COUNTRIES - Citra Noviasari; Sri Umiyati; M Husni Tamrin; Elli Setiyo Wahyuni (POLITEKNIK LP3I JAKARTA, 2026)
Coastal zone management is one of the most pressing governance challenges for nations with extensive coastlines amid accelerating climate change. This study aims to examine the lessons learned from Germany's coastal governance experience and to assess their relevance for developing archipelagic countries, particularly Indonesia. A comparative descriptive-analytical method was applied, drawing on official German policy documents, peer-reviewed literature, and reports from international institutions such as UNESCO, EUCC, and HELCOM. The results show that Germany's coastal governance success rests on six mutually reinforcing pillars: strong legal frameworks, long-term investment beyond political cycles, recognition of ecosystems as economic infrastructure, robust monitoring systems, transboundary coordination, and substantive community participation. These findings indicate that effective coastal governance is determined less by income level than by institutional commitment and policy coherence. The implication for Indonesia is the need to strengthen inter-agency coordination, adopt ecosystem-based adaptation, and formally recognize traditional community-based coastal governance systems as legitimate co-management mechanisms.